Literature Review: Efektifitas Intervensi Keperawatan Berbasis Group Counseling pada Klien Rehabilitasi Narkoba - Aeni, Nurul; Ashriady, Ashriady; Amaliah, Resky (Mando Care Jurnal, 2023)
Drugs today are urgent and complex. Many young people, teenagers and the elderly are involved in drug abuse. The impact of drug use is addiction and dependence. In dealing with these addictions and dependencies, rehabilitation is needed to increase motivation to recover and stop substance abuse. The role of nurses in drug rehabilitation will certainly be very helpful in providing nursing interventions. As for what can be done in providing interventions, namely group counseling based. The purpose of this study was to determine the effectiveness of group counseling-based nursing interventions on motivation to recover for drug rehabilitation clients. The method used in this study is a literature review using 8 articles based on the issue, methodology, and research similarities. Literature search using pubmed and google schooler. Of the 8 articles using research with qualitative and descriptive methods. The results showed that from 8 articles, group counseling-based nursing interventions were found to be effective in increasing motivation to recover in drug rehabilitation clients. It can be concluded that the entire article shows that nursing interventions based on group counseling can be used as reference material and referrals in drug rehabilitation services to increase motivation to recover and their readiness to stop substance abuse.